2018
DOI: 10.1108/jstp-01-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Customer value co-creation over the relationship life cycle

Abstract: Purpose Drawing from the theory of relationship dynamics, the purpose of this paper is to investigate how the relationship life cycle moderates the link between relationship quality and customer value co-creation. As customer-firm relationships pass through different stages (exploration, buildup, maturity, and decline) characterized by distinct customer behaviors, this study proposes a dynamic conceptual framework. Design/methodology/approach A questionnaire was administered in financial services firms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 82 publications
1
49
0
2
Order By: Relevance
“…Today's consumers play a much more active role in information/recommendation-seeking and decision-making processes (Cambra-Fierro et al 2018a). Many are even willing to co-create throughout design and service delivery processes (Lee 2019;Cambra-Fierro et al 2018b). These actions are grouped under the umbrella term, customer engagement, defined by van Doorn et al ( 2010) as a set of non-transactional behaviors springing from consumer motivational aspects, which have a deferred impact on the commercial outcome of the relationship.…”
Section: From Customer-based Brand Equity To Customer Engagement In Experiential Services: the Case Of Emerging Latam Economiesmentioning
confidence: 99%
“…Today's consumers play a much more active role in information/recommendation-seeking and decision-making processes (Cambra-Fierro et al 2018a). Many are even willing to co-create throughout design and service delivery processes (Lee 2019;Cambra-Fierro et al 2018b). These actions are grouped under the umbrella term, customer engagement, defined by van Doorn et al ( 2010) as a set of non-transactional behaviors springing from consumer motivational aspects, which have a deferred impact on the commercial outcome of the relationship.…”
Section: From Customer-based Brand Equity To Customer Engagement In Experiential Services: the Case Of Emerging Latam Economiesmentioning
confidence: 99%
“…Also, the findings of Verhoef, Franses, and Hoekstra (2002) suggest that the age of the relationship increases the positive effect of satisfaction and commitment on the number of services purchased. Cambra-Fierro et al (2018) showed that in the buildup and maturity stages, the impact of relationship quality on customer value co-creation was stronger than in the decline stage.…”
Section: Moderating Effect Of the Relationship Lifecycle On The Qualimentioning
confidence: 99%
“…Morgan and Hunt (1994) view commitment as being at the heart of successful long-term relationships. Given that commitment is a basic variable in measuring the future of seller-purchaser relationships, most studies on relationship marketing have treated it as an important dimension of relationship quality (Brun et al, 2014;Cambra-Fierro, Melero-Polo, & Javier 2018;De Wulf et al, 2001;De Wulf et al, 2003;Hennig-Thurau et al, 2002;Palmatier, 2006;Roberts, Varki, & Brodie 2003;See Dorsch, 1998;Wang et al, 2006). Berry and Parasurman (1991) define commitment as a vital part of a successful relationship that can foster loyalty.…”
Section: Online Trustmentioning
confidence: 99%
“…For example, Vakulenko, Hellström, and Oghazi (2018), suggest identifying new sources of competitive advantage and new ways to improve customer service strategies and experience management. Cambra-Fierro et al (2018), suggest that as the customer relationship stage continues to develop, companies must also develop attractive additional tools to personalize business strategies and tailor marketing investments to specific customer situations. Fu et al (2017), stated that effective marketing strategies to increase customer value if they understand the nature and impact of quantitative data and qualitative information regarding influencing factors.…”
Section: Previous Researchmentioning
confidence: 99%